ANALISIS PENGELOLAAN KEUANGAN KALURAHAN SARIHARJO TAHUN 2025 BERDASARKAN PERMENDAGRI 20/2018 - Salsabilla De Alya; Yulia Larasati Putri; Alfiyah; Novia Pungky Saputri; Eka Permata Nuraini (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to analyze the compliance of village financial management with the Regulation of the Minister of Home Affairs Number 20 of 2018 in Kalurahan Sariharjo for the 2025 fiscal year and to identify existing challenges. The research employs a qualitative descriptive case study approach, collecting data through interviews and documentation. The results show that the financial management of Kalurahan Sariharjo is generally in accordance with the regulation, including budget structure, management stages, and transparency. Key strengths include the use of Siskeudes, multi-channel transparency, community participation, and revenue diversification. However, challenges remain, including inconsistencies between planning and implementation, low village own-source revenue, the dominance of infrastructure spending, and administrative complexity.